ETV in tuberculous meningitis with hydrocephalus and allergic reaction to VP shunt: a case report - Rosyidi, Rohadi M.; Priyanto, Bambang; Parenrengi, Muhammad Arifin (International Journal of Research in Medical Sciences, 2018)
Hydrocephalus is one of the most common complications of tuberculous meningitis (TBM) occurring in up to 85% of patients with the disease. The placement of a ventriculoperitoneal (VP) shunt is the most common form of treatment for hydrocephalus in tuberculous meningitis (TBM). Although allergic reactions to the silicone in shunt device are very rare, the authors describe a case of silicone allergy causing multiple VP shunt revisions. Alternative choice is endoscopic third ventriculostomy (ETV), but it is debatable. ETV has variable success in these patients and is generally not advisable in patients in the acute stages of the disease. A 19-year-old woman with hydrocephalus in tuberculous meningitis, who had undergone multiple VP shunt revisions, presented with shunt malfunction caused by allergic reaction of the tissue surrounding the shunt tubing. Laboratory examination demonstrated high level IgE, high level ESR, and PCR-TBC Positive, related to the allergic reaction. Patient with ETV success score of 50. Patients received ETV and release VSS Shunt. ETV has success in these patients. VP Shunts complications remain a difficult problem in neurosurgical clinical practice. The most typical complications are mechanical obstruction and infection. Allergy to the silicone shunt tubing is quite rare. Silicone allergy is an even more rare occurrence because of its high biocompatibility and low biological reactivity. It is a challenge for ETV when TBM has difficulty to recognize anatomical landmarks on this patient. It could also consider in patients who have shunt failure, and might be a better option than shunt revision.